(Re)mapping women’s cosmology : transformative potentia of women’s stories : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Whanganui-a-tara/Wellington, Aotearoa/New Zealand - Wass, Thea (Massey University, 2023)
Binary difference is deeply rooted within the heart of European philosophy and underpins contemporary understandings of sexual difference. Forces of power relations circulate to uphold binary categories of gender that conflates man with the universal, upholding a single model of male subjectivity and inscribing meaning onto the bodies of women. In this research, I have engaged with a narrative approach to map a cosmology of ten women’s stories, connecting women’s bodies and experiences to the flow of forces that shape their lives through a complex assemblage of cultural practices. Thinking with Rosie Braidotti I have endeavoured to sketch a cartography of the multiple embedded, embodied and affective social positions constituted by forces operational in, and immanent to the production and circulation of knowledge about sexual difference. Relational ethics in feminist standpoint inquiry enabled me to attend to relational processes which contributed to the co-articulation of these stories, and to open out towards the multiple possibilities available outside established hierarchical categories of gendered subjectivities. Through this process, light is cast on the material conditions in which forces come to inscribe and inhabit women’s bodies as flows of power capable of both “entrapment (potestas) and as empowerment (potentia)” (Braidotti, 2019). This research resists phallogocentric notions of the universal by re-orienting towards the affirmative potential of women’s bodies made available through interconnectedness and ethical transformation in processes of becoming. By paying attention to the situated and affirmatively encompassing differences within and between women, bodies can be understood as a site of resistance and transformation.
Keywords: Sex role; Patriarchy; Psychological aspects; Women; Psychology; Anecdotes; Self-actualization (Psychology) in women; Male domination (Social structure); Dominance (Psychology); Power (Social sciences); sexual difference; power relations; relational ethics; feminist standpoint; cartography (Psychology); 441010 Sociology of gender; 520302 Clinical psychology